PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PONDOK PESANTREN MODERN ISLAM ASSALAAM SURAKARTA - -, Sidiq -; Suddin, Alwi - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2013)
The purposes of this research are to analyze the significant impact of: (1) leadership variable to job satisfaction, (2) organization motivation variable to job satisfaction, (3) organizational commitment variable to job satisfaction, (4) the dominant variable that have impact to job satisfaction. Populations of this research are 125 employees in Pondok Pesantren Modern Islam Assalaam Surakarta. The samples of this research are 63 employees with sampling technique used is opinion poll method. To collect data the writer used questionnaire with validity and reliability examination. The methods to analyze data are double regression linear with classic assumption. The conclusions from the result of the research: (1) the hypothesis stated that â€œleadership has positive impact and significant to job satisfactionâ€ is verified, (2) the hypothesis stated that â€œorganization motivation has positive impact and significant to job satisfactionâ€ is not verified, (3) the hypothesis stated that â€œorganizational commitment has positive impact and significant to job satisfactionâ€ is verified, (4) the hypothesis stated that â€œleadership has dominant impact to job satisfactionâ€ is not verified. Keywords: leadership, motivation, organizational commitment, job satisfaction